Application of Real Options Techniques to Project Valuation and Company Valuation - HAN, YAN (2013)
This dissertation explores the valuation techniques provided by real options theory through applying the technique into assessing the value of investment opportunities and the value of company. As one of the most prevalent pricing theory, as opposed to traditional DCF approach, real option theory takes into account the flexibilities of managing projects when facing the uncertain market condition. By excavating the potential value hiding in the project’s option, the evaluation of a project will acquire a substantial increase. Besides, the recent development in the real options technique allows the valuation of a company. After literature review, which includes the basic concept and types of real options, the core option-pricing approaches will be elaborated along with a further discussion of real options theory. The main part focuses on the valuation of investment opportunities and the assessment on the value of an IT company, Hewlett-Packard Development Company. The dissertation mainly uses binomial tree method in estimating the value of investment opportunities as well as Black-Scholes model where it is necessary. For the R&D project, which needs multi-stage decision-making, the compound option model developed by Geske(1979)is applied to assess its value.